2003
DOI: 10.1074/jbc.m209755200
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Conformation State of Cytochrome b 558 Initiates NADPH Oxidase Activation

Abstract: The phagocyte respiratory burst depends on the NADPH reduction of molecular oxygen and generation of superoxide anion O 2 . upon activation of the cell with soluble (chemotactic factors) or particulate (bacteria or fungi) stimuli (1). The O 2 . -generating NADPH oxidase (EC 1.6.99.6) is a heterogeneous complex compartmentalized in resting cells, between plasma membrane, cytosol, and the cytoskeleton, which assembles at the plasma membrane level once activated. Cytochrome b 558 is the membrane redox core of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(97 citation statements)
references
References 56 publications
5
90
0
2
Order By: Relevance
“…Phosphorylation has been implicated in translocation of the MRP-14/ MRP-8 heterodimer to membranes and cytoskeleton in monocytes (30). MRP-14 was also reported to participate in the initiation of NADPH oxidase activity in human neutrophils (31,32). The present study showed that p38 MAPK phosphorylates MRP-14 on Thr 113 .…”
supporting
confidence: 50%
See 3 more Smart Citations
“…Phosphorylation has been implicated in translocation of the MRP-14/ MRP-8 heterodimer to membranes and cytoskeleton in monocytes (30). MRP-14 was also reported to participate in the initiation of NADPH oxidase activity in human neutrophils (31,32). The present study showed that p38 MAPK phosphorylates MRP-14 on Thr 113 .…”
supporting
confidence: 50%
“…The MRP-14/MRP-8 complex was reported to undergo phosphorylation-dependent translocation to the plasma membrane and cytoskeleton in monocytes after cell stimulation (30). The MRP-14/MRP-8 complexes were also found to bind arachidonic acid (38,39) and to participate in the activation of NADPH oxidase (31,32). MRP-14/MRP-8 increased the affinity of p67 phox for cytochrome b 558 , and oxidase activity was enhanced (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The capacity of electron transfer in vitro was evaluated using an adapted protocol previously described [17]. Briefly, 10 pmol of purified proteins was incubated for 5 min at 4°C in PBS buffer containing 10 lM FAD (with or without 300 lg of cytosol isolated from HEK293E cells) and 100 lM INT (iodonitro tetrazolium chloride) or 100 lM cytochrome c. The reaction was initiated by the addition of 150 lM NADPH, and the reduction of these compounds was followed during 30 min (at 500 nm for INT, e 500nm = 11 mM À1 cm À1 or at 550 nm for cytochrome c, e 550nm = 21.1 mM À1 cm À1 ).…”
Section: Cell-free System Diaphorase Activity Assaymentioning
confidence: 99%